The teaching of bioethics at the medical school of the Pontifical Catholic University of Argentina - Revello, Rubén Oscar (Medicina e Morale, 2025)
The article considers it essential for medical schools to incorporate bioethics into the curriculum of all future doctors. Respect for the patient, clarity in medical communication, and a professional and empathetic attitude are considered indispensable for medical practice. This has been understood by almost all medical schools around the world, which have been adding bioethics to their curricula. The methodology used for teaching bioethics at the Faculty of Medicine of the Pontifical Catholic University of Argentina is described. If giving technical training is complex, it is much more complex to transmit a series of ethical values that the future doctor must not only know, but also incorporate personally into his or her scheme of values. This makes teaching bioethics an arduous process, a personal journey that goes from knowledge to critical analysis, from personal criticism to internal adherence, and from the incorporation of these values to their application in the various concrete situations of medical practice. We describe a study carried out to evaluate the levels of adherence to medical humanism and commitment to the practice of medicine, under a specific aspect, which is bioethical training.